2006
DOI: 10.1016/j.bbabio.2006.04.001
|View full text |Cite
|
Sign up to set email alerts
|

On the localized coupling of respiration and phosphorylation in mitochondria

Abstract: This paper is an overview of the theoretical and experimental studies performed in our laboratory to answer the question whether there exist conditions where the hypothetical mechanism of the localized coupling of respiration and phosphorylation postulated by R. Williams in 1961 operates. These studies were undertaken to verify the earlier suggestion that mitochondria may exist in two structural and functional states. Correspondingly, there are two operation modes of oxidative phosphorylation, one of which cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Likewise, specific respiratory supercomplexes were detected by similar approaches in mitochondria of various eukaryotes (15,26,27,45,47,61,62,64,71,94,97,98), including the filamentous fungus Podospora anserina (45), as well as in bacteria (79). Recently, the first single particle structures of respiratory supercomplexes were determined (24,39,66), and several other important studies by the bioenergetics/ mitochondrial community have supported the respirasome model (1,6,10,18,21,49,56,62,85,86,88,96). However, the functional significance of respiratory supercomplexes, including their enzymatic advantages, is still poorly documented.…”
mentioning
confidence: 88%
“…Likewise, specific respiratory supercomplexes were detected by similar approaches in mitochondria of various eukaryotes (15,26,27,45,47,61,62,64,71,94,97,98), including the filamentous fungus Podospora anserina (45), as well as in bacteria (79). Recently, the first single particle structures of respiratory supercomplexes were determined (24,39,66), and several other important studies by the bioenergetics/ mitochondrial community have supported the respirasome model (1,6,10,18,21,49,56,62,85,86,88,96). However, the functional significance of respiratory supercomplexes, including their enzymatic advantages, is still poorly documented.…”
mentioning
confidence: 88%
“…In that work it was found that activation of Н + pumps decreases nega tive ζ potential and a catalyst (HEPES) is able to elim inate this effect. In a previous work [3] it was shown that catalyst (HEPES 20 mM) significantly increases the maximum value of the transmembrane flux of H + ions.…”
Section: Introductionmentioning
confidence: 92%
“…In our previous works [3,4], the formation of metastable fraction of hydrogen ions possessing an excess of free energy was demonstrated on the mem brane surface of mitoplasts [5] and mitochondria [6]. Membrane bound protons stay in a non equilibrium state and participate in the reaction of the ATP synthe sis [3,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that the solvation potential energy could be used for synthesis of ATP and that the catalyst of [12,16]. This result suggested that the fraction of membrane bound protons was involved in the synthe sis of ATP.…”
Section: Fraction Of "Energized" Protons On the Surface Of Membranes mentioning
confidence: 97%